Composite reverse osmosis membrane and preparation method thereof
Through additive manufacturing technology, alternating spraying of m-phenylenediamine, phenylenediamine and triformyl chloride and covalent organic frame materials in reverse osmosis membranes has solved the problem of difficult to take into account both the flux and selectivity of the reverse osmosis membrane in the prior art, and achieved high efficiency The water molecule transmission and salt removal improve the membrane's anti-pollution performance and environmental protection.
Patent Information
- Application Number
- CN202411536461.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-03
Smart Images

Figure CN119236679A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of reverse osmosis membranes, and in particular to a composite reverse osmosis membrane and a preparation method thereof. Background Art
[0002] Reverse osmosis membrane separation technology is a membrane separation process driven by pressure difference. It can achieve efficient separation of water and other substances. The separation process does not involve energy-intensive phase change. It has the advantages of high separation efficiency, simple operation, short construction cycle and environmental friendliness. It has been widely used in seawater desalination, pure water preparation, and pharmaceutical and chemical wastewater treatment. Reverse osmosis membrane is the core of this separation technology, which requires the membrane to maintain a high water permeability under high retention rate.
[0003] The reverse osmosis membrane of the prior art is generally a polyamide thin film composite reverse osmosis (TFC RO) membrane prepared by an immersion process interfacial polymerization method on the surface of a porous support membrane. The preparation process is based on the rapid self-limiting polymerization reaction of two membrane-forming monomers, m-phenylenediamine (MPD) and trimesoyl chloride (TMC), at the water / n-hexane two-phase interface. Since the diffusion and reaction of the two monomers are difficult to intervene artificially during the polymerization reaction, the adjustability of the film thickness, pore size and distribution is poor, and it is impossible to achieve high flux and high selectivity at the same time, which restricts the further improvement of its separation performance. The membrane flux can be improved by doping in the separation layer. For example, the Hoek group of the University of California, Los Angeles and the Yan group of the University of California, Riverside, collaborated to fill nano-scale molecular sieves into polyamide reverse osmosis composite membranes, which increased the water flux of the membrane by nearly two times, while the salt retention rate remained basically unchanged, and the concept of ultra-thin nano-composite reverse osmosis membranes was first proposed (J. Membr. Sci., 2007, 294, 1). In recent years, some researchers have embedded nanomaterials with unique pores or surface structures, such as zeolite molecular sieves, metal organic framework nanoparticles, graphene, carbon nanotubes, and aquaporins into polyamide reverse osmosis composite membranes to improve water flux (Desalination, 2013, 308, 34). However, there are problems such as poor doping controllability, extremely low utilization of nanomaterials, and great waste of raw materials. On the other hand, the surface structure of the membrane prepared by traditional interfacial polymerization is rough, and the charge on the surface and inside of the membrane is uncontrollable due to the difficulty in controlling the degree of polymerization, which brings serious membrane pollution problems and is difficult to solve by effective methods; at the same time, the traditional interfacial polymerization process uses a large amount of organic solvents, and the utilization rate of film-forming monomers is low, which does not meet the needs of low-carbon environmental protection and clean production. Therefore, how to improve the preparation process of nanocomposite membranes and prepare reverse osmosis membranes with uniform particle distribution, no aggregation, and excellent performance is one of the important issues that need to be solved in the field of nanocomposite films. Summary of the invention
[0004] In order to solve the above technical problems, the primary purpose of the present invention is to provide a method for preparing a composite reverse osmosis membrane. The preparation method is based on additive manufacturing technology, and nanoparticles are uniformly and controllably doped into a polyamide separation layer to obtain a thin film nano-composite reverse osmosis membrane.
[0005] A further object of the present invention is a composite reverse osmosis membrane prepared by the above method.
[0006] The above object of the present invention is achieved through the following technical solutions:
[0007] A method for preparing a composite reverse osmosis membrane comprises the following steps:
[0008] (1) fixing the porous support membrane on the collector of the electrostatic spray device, spraying the m-phenylenediamine solution and the trimesoyl chloride solution on the porous support membrane by the electrostatic spray device, and then spraying the covalent organic framework material dispersion containing polar functional groups, and the two sprayings are alternately performed several times to obtain an initial covalent organic framework reverse osmosis membrane;
[0009] (2) post-treating the initial covalent organic framework reverse osmosis membrane obtained in step (1) to remove unreacted m-phenylenediamine and trimesoyl chloride to obtain the composite reverse osmosis membrane.
[0010] In view of the technical problem that the interface force between traditional inorganic nanomaterials and polyamide materials is weak and easily leads to defects, the present invention selects porous covalent organic framework materials as additive materials. The advantage of covalent organic framework materials is that they have rich functional groups and can be combined with polyamide materials through chemical bonds or hydrogen bonds to avoid the generation of defects; and the covalent organic framework materials themselves have the advantages of high porosity, regular pore structure, stable chemical properties, etc., so that the prepared composite reverse osmosis membrane has excellent salt retention rate and high water flux.
[0011] In addition, in order to achieve uniform and controllable doping of the porous covalent organic framework material in the polyamide separation layer, the present invention adopts an electrostatic spray-assisted additive manufacturing method, that is, the precursor (metaphenylenediamine and trimesoyl chloride) solution of the polyamide membrane and the covalent organic framework material dispersion are sprayed alternately on the surface of the porous support membrane by electrostatic spraying. Metaphenylenediamine and trimesoyl react to form a polyamide membrane. In the process of generating the polyamide membrane, the covalent organic framework material is uniformly doped therein, and the doping amount in the polyamide membrane is regulated by adjusting the concentration of the covalent organic framework material dispersion. The thin film nanocomposite reverse osmosis membrane based on additive manufacturing technology has a smoother surface, so its anti-pollution performance is further improved.
[0012] Furthermore, in step (1), the porous support membrane is a polysulfone porous support membrane, a polyethersulfone porous support membrane or a polyacrylonitrile porous support membrane, preferably a polyethersulfone porous support membrane.
[0013] Furthermore, in step (1), the volume ratio of the m-phenylenediamine solution to the trimesoyl chloride solution is 1:(0.5-1.5).
[0014] Furthermore, in step (1), the polar functional group includes an amine group, an imine group, etc.
[0015] Furthermore, in step (1), the covalent organic framework material is selected from one or more of particles with a particle size of 5-40 nm, nanosheets with a thickness of 1-10 nm, and nanowires with a diameter of 1-10 nm.
[0016] Furthermore, in step (1), the covalent organic framework material can be DABA-TFP nanosheets, CC3 organic molecular cage nanoparticles, TpPa nanosheets, etc.
[0017] Furthermore, in step (1), the concentration of the m-phenylenediamine solution is 0.1-8.0 mg / mL.
[0018] Furthermore, in step (1), the m-phenylenediamine solution is prepared by dissolving m-phenylenediamine in a water / methanol mixed solvent, wherein methanol accounts for 10%-50% of the volume of the water / methanol mixed solvent.
[0019] Furthermore, in step (1), the concentration of the trimesoyl chloride solution is 0.1-2.0 mg / mL.
[0020] Furthermore, in step (1), the trimesoyl chloride solution is prepared by dissolving trimesoyl chloride in a n-hexane / acetone mixed solvent, wherein the acetone accounts for 10%-50% of the volume of the n-hexane / acetone mixed solvent.
[0021] Furthermore, in step (1), the concentration of the covalent organic framework material dispersion is 0.01-0.2 mg / mL.
[0022] Furthermore, the concentration of the DABA-TFP nanosheet dispersion is preferably 0.05-0.45 mg / mL.
[0023] Furthermore, in step (1), the covalent organic framework material dispersion is prepared by ultrasonically dispersing the covalent organic framework material in a solvent.
[0024] Furthermore, the solvent may be methanol, ethanol, acetone, etc.
[0025] Furthermore, in step (1), the two spraying steps are performed alternately for 6 to 10 times.
[0026] In a specific embodiment, the m-phenylenediamine solution and the trimesoyl chloride solution are respectively loaded into a syringe and placed on a movable device of an electrostatic spray device, the porous support membrane is infiltrated from the bottom with an infiltration liquid and fixed on a collector of the electrostatic spray device, and under the action of an electric field, two monomer (m-phenylenediamine, trimesoyl chloride) solutions are sprayed on the porous support membrane, and the syringe moves from one end to the other end and then returns to the initial position, which is recorded as "one scan". After completing the spraying process of the m-phenylenediamine solution and the trimesoyl chloride solution, the covalent organic framework material dispersion is replaced and sprayed once. Then the m-phenylenediamine solution and the trimesoyl chloride solution are sprayed again, and after repeated alternate spraying for a certain number of times, an initial covalent organic framework reverse osmosis membrane is obtained.
[0027] Furthermore, the infiltration liquid is a mixed solution of water and ethylene glycol, wherein the volume proportion of ethylene glycol is 30%-60%.
[0028] Furthermore, the applied electric field voltage is 6-15 kV.
[0029] Furthermore, in each spraying process, the monomer solution is scanned 5-15 times, and the covalent organic framework material dispersion is scanned 3-10 times.
[0030] Furthermore, in step (2), the specific method of the post-treatment is: immersing the initial covalent organic framework reverse osmosis membrane in a sodium persulfate aqueous solution and a sodium hydroxide aqueous solution in sequence.
[0031] Furthermore, the concentration of the sodium persulfate aqueous solution is 20-50 g / L.
[0032] Furthermore, the concentration of the sodium hydroxide aqueous solution is 5-20 g / L.
[0033] In a specific embodiment, in step (2), the initial covalent organic framework reverse osmosis membrane is immersed in a 50-60° C. sodium persulfate hot water bath and a 80-90° C. sodium hydroxide hot water bath in sequence.
[0034] Furthermore, in step (2), after the post-treatment is completed, a drying step is also included.
[0035] The present invention also protects a composite reverse osmosis membrane prepared by the method.
[0036] Beneficial effects of the present invention:
[0037] 1. The present invention adopts an additive manufacturing method to prepare a composite reverse osmosis membrane, which can achieve controllable doping of the reverse osmosis membrane, and the doped particles are evenly distributed without agglomeration. The preparation process is simple, the conditions are mild, and it is easy to scale up and promote.
[0038] 2. The composite reverse osmosis membrane prepared by the present invention utilizes the specific size pore structure of the covalent organic framework material to allow water molecules to pass through while effectively rejecting salt ions, so it has a higher water flux and salt rejection rate. In addition, the surface of the composite reverse osmosis membrane is smooth and has good anti-pollution performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 Schematic diagram of the electrostatic spraying process in Example 1 of the present invention.
[0040] Figure 2 This is the surface SEM image of the composite reverse osmosis membrane prepared in Example 2.
[0041] Figure 3 This is a cross-sectional TEM image of the composite reverse osmosis membrane prepared in Example 2.
[0042] Figure 4 This is a graph showing the anti-pollution performance test results of the composite reverse osmosis membrane prepared in Example 2; wherein a is sodium dodecyl sulfate and b is sodium alginate.
[0043] Figure 5 The figure is a data comparison chart of the rejection rate and flux of the reverse osmosis membranes prepared in Examples 1-4 and Comparative Example 1. DETAILED DESCRIPTION
[0044] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0045] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0046] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.
[0047] The covalent organic framework material in the following example is homemade in the laboratory, and the preparation method is as follows: 0.42g of p-aminobenzenesulfonic acid (DABA) and 0.56g of trialdehyde phloroglucinol (TFP) are dissolved in 50mL of dimethyl sulfoxide and reacted at room temperature for 24 hours. Then, the organic solvent and unreacted monomers are removed by dialysis using a dialysis bag. Finally, the dialyzed solution is freeze-dried by a freeze-drying method to obtain DABA-TFP nanosheets.
[0048] Example 1
[0049] A method for preparing a composite reverse osmosis membrane comprises the following steps:
[0050] (1) DABA-TFP nanosheets were dispersed in methanol to prepare a DABA-TFP nanosheet dispersion with a concentration of 0.05 mg / mL; m-phenylenediamine was dissolved in a water / methanol mixed solvent to prepare a m-phenylenediamine solution with a concentration of 4.0 mg / mL, wherein the methanol content in the mixed solvent was 40%; trimesoyl chloride was dissolved in a n-hexane / acetone mixed solvent to prepare a trimesoyl chloride solution with a concentration of 0.9 mg / mL, wherein the acetone content in the mixed solvent was 40%;
[0051] The m-phenylenediamine solution and the trimesoyl chloride solution are respectively loaded into syringes and placed on a movable device of the electrostatic spraying device, such as Figure 1 As shown, a polyethersulfone ultrafiltration membrane with a molecular weight cutoff of 30 kDa was infiltrated with 30% ethylene glycol from the bottom for 20 minutes and then fixed on the collector of an electrostatic spray device. Under the action of an electric field, a voltage of 10 kV was applied, and a m-phenylenediamine solution and a trimesoyl chloride solution were sprayed on the porous support membrane. After 10 scans, the DABA-TFP nanosheet dispersion was replaced and scanned 5 times. This alternation was repeated 8 times to obtain an initial covalent organic framework reverse osmosis membrane having five polyamide layers and four nanosheet layers.
[0052] (2) The initial covalent organic framework reverse osmosis membrane obtained in step (1) was placed in a 35 g / L sodium persulfate hot water bath at 50°C and soaked for 5 hours. Finally, the membrane was placed in a 15 g / L sodium hydroxide hot water bath at 90°C and soaked for 2 hours to obtain a composite reverse osmosis membrane, named M1 membrane.
[0053] The reverse osmosis performance of the M1 membrane was evaluated by placing the M1 membrane in a cross-flow filtration device with a test area of 7.07 cm 2 The retention rate and flux of the membrane were measured at 25°C and 1.5MPa, and the salt solution used was 2000ppm NaCl solution. The test results showed that the retention rate of the M1 membrane could reach 96.6% and the flux could reach 1.7L·m -2 ·h -1 bar -1 .
[0054] Example 2
[0055] A method for preparing a composite reverse osmosis membrane is basically the same as that of Example 1, except that in step (1), the concentration of the DABA-TFP nanosheet dispersion is 0.15 mg / mL, and the composite reverse osmosis membrane finally prepared is named M2 membrane.
[0056] Figure 2 This is a surface scanning electron microscope (SEM) image of the composite reverse osmosis membrane prepared in Example 2. It can be observed that the membrane surface has a dense and smooth structure. Figure 3 This is a transmission electron microscope (TEM) image of the cross section of the composite reverse osmosis membrane prepared in Example 2. From the image, it can be seen that the COF nanomaterial is uniformly doped in the polyamide separation layer.
[0057] The reverse osmosis membrane performance of M2 membrane was evaluated using the same test method as in Example 1. The test results showed that the retention rate of M1 membrane could reach 96.5% and the flux could reach 2.1 L·m -2 ·h -1 bar -1 .
[0058] The anti-fouling performance of the M2 membrane was tested using two model pollutants, sodium dodecyl sulfate (SDS) and sodium alginate (SA). The test method was as follows: the M2 membrane was subjected to two "filtration-rinsing" cycles. One "filtration-rinsing" cycle included 3 hours of filtration and 1 hour of rinsing. In the first 30 minutes of the filtration process, the filtration performance of the membrane for NaCl solution was measured, and then the model pollutants SDS or SA were added to the NaCl solution to prepare a solution containing model pollutants with a concentration of 0.1 g / L. A flux test was conducted for 2.5 hours, and the water flux of the membrane was calculated by recording the permeation weight of the membrane every 10 minutes. After the filtration process, the contaminated solution was completely removed and replaced with pure water for 1 hour of rinsing. After the two "filtration-rinsing" cycles, the pure water in the system was replaced by a NaCl aqueous solution, and its flux was measured again for 30 minutes. The test results are as follows Figure 4 As shown in Figure 2, after continuous filtration of solutions containing SDS or SA model pollutants, the pure water flux of the membrane was restored to 1.96 and 1.97 L·m, respectively, after cleaning. -2 ·h -1 bar -1 , and the recovery rates were 93.4% and 93.7% respectively, which proves that the composite reverse osmosis membrane prepared by the present invention has good anti-pollution performance.
[0059] Example 3
[0060] A method for preparing a composite reverse osmosis membrane is basically the same as Example 1, except that in step (1), the concentration of the DABA-TFP nanosheet dispersion is 0.30 mg / mL, and the composite reverse osmosis membrane finally prepared is named M3 membrane.
[0061] The reverse osmosis performance of the M3 membrane was evaluated using the same test method as in Example 1. The test results showed that the retention rate of the M3 membrane could reach 96.9% and the flux could reach 1.9 L·m -2 ·h -1 bar-1 .
[0062] Example 4
[0063] A method for preparing a composite reverse osmosis membrane is basically the same as that of Example 1, except that in step (1), the concentration of the DABA-TFP nanosheet dispersion is 0.45 mg / mL, and the composite reverse osmosis membrane finally prepared is named M4 membrane.
[0064] The reverse osmosis performance of the M4 membrane was evaluated using the same test method as in Example 1. The test results showed that the retention rate of the M4 membrane was 96.6% and the flux was 1.8 L·m -2 ·h -1 bar -1 Comparative Examples 1-4 show that as the concentration of the DABA-TFP nanosheet dispersion increases, the water flux increases first and then gradually decreases, indicating that excessive nanosheet doping will reduce the water flux, and M2 is the optimal doping result.
[0065] Example 5
[0066] A method for preparing a composite reverse osmosis membrane is basically the same as that of Example 1, except that in step (1), the DABA-TFP nanosheet dispersion is replaced with a CC3 organic molecular cage nanoparticle dispersion with a concentration of 0.2 mg / mL, and finally a composite reverse osmosis membrane doped with CC3 organic molecular cage nanoparticles is prepared.
[0067] The performance of the composite reverse osmosis membrane doped with CC3 organic molecular cage nanoparticles was evaluated. The test method was the same as that in Example 1. The test results were as follows: the NaCl rejection rate of the composite reverse osmosis membrane doped with CC3 organic molecular cage nanoparticles was 96.1%, and the flux was 2.0 L·m -2 ·h -1 bar -1 , indicating that the addition of CC3 organic molecular cages can also construct water molecule transmission channels, the water flux is improved, and the retention rate of NaCl remains unchanged.
[0068] Example 6
[0069] A method for preparing a composite reverse osmosis membrane is basically the same as Example 1, except that in step (1), the DABA-TFP nanosheet dispersion is replaced with a TpPa nanosheet dispersion with a concentration of 0.2 mg / mL, and finally a TpPa nanosheet-doped composite reverse osmosis membrane is prepared.
[0070] The performance of the composite reverse osmosis membrane doped with TpPa nanosheets was evaluated. The test method was the same as that in Example 1. The test results showed that the NaCl rejection rate of the composite reverse osmosis membrane doped with TpPa nanosheets was 96.3%, and the flux was 1.9 L·m -2 ·h -1 bar -1 , indicating that the addition of TpPa nanosheets can also construct water molecule transmission channels, the water flux is improved, and the retention rate of NaCl remains unchanged.
[0071] Comparative Example 1
[0072] A method for preparing a reverse osmosis membrane comprises the following steps:
[0073] Metaphenylenediamine was dissolved in a water / methanol mixed solvent to prepare a metaphenylenediamine solution with a concentration of 4.0 mg / mL, in which methanol accounted for 40% of the mixed solvent; trimesoyl chloride was dissolved in a n-hexane / acetone mixed solvent to prepare a trimesoyl chloride solution with a concentration of 0.9 mg / mL, in which acetone accounted for 40% of the mixed solvent; the metaphenylenediamine solution and the trimesoyl chloride solution were respectively loaded into syringes and placed on a movable device of an electrostatic spray device, a polyethersulfone ultrafiltration membrane with a molecular weight cutoff of 30 kDa was infiltrated from the bottom with 30% ethylene glycol for 20 minutes and then fixed on the collector of the electrostatic spray device, under the action of an electric field, a voltage of 10 kV was applied, and the metaphenylenediamine solution and the trimesoyl chloride solution were sprayed on the porous support membrane, and after 50 scans, a reverse osmosis membrane was obtained, which was named M0 membrane.
[0074] The reverse osmosis membrane performance of the M0 membrane was evaluated using the same test method as in Example 1. The test results showed that the retention rate of the M4 membrane could reach 96.2% and the flux could reach 1.4 L·m -2 ·h -1 bar -1 .
[0075] Figure 5 The figure is a data comparison chart of the rejection rate and flux of the reverse osmosis membranes prepared in Examples 1-4 and Comparative Example 1.
[0076] Comparative Example 2
[0077] A method for preparing a composite reverse osmosis membrane is basically the same as that of Example 1, except that in step (1), the DABA-TFP nanosheet dispersion is replaced with a graphene oxide dispersion with a concentration of 0.15 mg / mL, and finally a graphene oxide-doped composite reverse osmosis membrane is prepared.
[0078] The performance of the composite reverse osmosis membrane doped with graphene oxide was evaluated. The test method was the same as that in Example 1. The test results showed that the rejection rate of the composite reverse osmosis membrane doped with graphene oxide could reach 96.0%, and the flux could reach 0.8 L·m -2 ·h -1 bar -1 Since graphene oxide has a dense structure, it hinders the penetration of water after doping, reducing the water flux of the composite reverse osmosis membrane.
[0079] Comparative Example 3
[0080] A method for preparing a composite reverse osmosis membrane is basically the same as that of Example 1, except that in step (1), the DABA-TFP nanosheet dispersion is replaced with a CuBDC (BDC is terephthalic acid) metal organic framework nanosheet dispersion with a concentration of 0.15 mg / mL, and finally a CuBDC metal organic framework nanosheet-doped composite reverse osmosis membrane is prepared.
[0081] The performance of the composite reverse osmosis membrane doped with CuBDC metal organic framework nanosheets was evaluated. The test method was the same as that in Example 1. The test results showed that the rejection rate of the composite reverse osmosis membrane doped with graphene oxide could reach 95.5%, and the flux could reach 1.3 L·m -2 ·h -1 bar -1 By electron microscopy, no doped CuBDC MOF nanosheets were found in the polyamide separation layer, probably because the MOF nanosheets were dissolved during the acid / base post-treatment and the doping effect was not achieved.
[0082] Comparative Example 4
[0083] A method for preparing a composite reverse osmosis membrane is basically the same as that of Example 1, except that in step (1), the DABA-TFP nanosheet dispersion is replaced with an MFI zeolite nanosheet dispersion with a concentration of 0.15 mg / mL, and finally a composite reverse osmosis membrane doped with MFI zeolite nanosheets is prepared.
[0084] The performance of the composite reverse osmosis membrane doped with MFI zeolite nanosheets was evaluated. The test method was the same as that in Example 1. The test results showed that the rejection rate of the composite reverse osmosis membrane doped with graphene oxide could reach 46.1%, and the flux could reach 5.3 L·m -2 ·h -1 bar -1 Although the MFI zeolite nanosheets have good chemical stability, they are not compatible with the polyamide separation layer, which leads to defects between the MFI zeolite nanosheets and the polyamide separation layer, thus reducing the salt retention performance.
[0085] In summary, the composite reverse osmosis membrane doped with the covalent organic framework material prepared by the present invention has a higher flux and a higher salt rejection rate than the composite reverse osmosis membrane doped with other materials. The reasons are: (1) The covalent organic framework material and the polyamide material are both organic materials, which can easily form a uniform composite under the action of chemical bonds or hydrogen bonds to avoid the occurrence of defects; (2) The covalent organic framework material itself has a regular porous structure, which constructs a rapid transmission channel for water molecules in the polyamide layer, thereby improving the separation flux; (3) The covalent organic framework material has better chemical stability and can withstand acid and alkali corrosion during the post-treatment process of the separation membrane.
[0086] Obviously, the above embodiments of the present invention are only examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. Those skilled in the art should understand that other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a composite reverse osmosis membrane, characterized in that: The following steps are involved: (1) fixing the porous support membrane on the collector of the electrostatic spray device, spraying the m-phenylenediamine solution and the trimesoyl chloride solution on the porous support membrane by the electrostatic spray device, and then spraying the covalent organic framework material dispersion containing polar functional groups, and the two sprayings are alternately performed several times to obtain an initial covalent organic framework reverse osmosis membrane; (2) post-treating the initial covalent organic framework reverse osmosis membrane obtained in step (1) to remove unreacted m-phenylenediamine and trimesoyl chloride to obtain the composite reverse osmosis membrane.
2. The preparation method according to claim 1, characterized in that: In step (1), the porous support membrane is a polysulfone porous support membrane, a polyethersulfone porous support membrane or a polyacrylonitrile porous support membrane.
3. The preparation method according to claim 1, characterized in that: In step (1), the covalent organic framework material is selected from one or more of particles with a particle size of 5-40 nm, nanosheets with a thickness of 1-10 nm, and nanowires with a diameter of 1-10 nm.
4. The preparation method according to claim 1 or 3, characterized in that: In step (1), the covalent organic framework material is selected from one or more of DABA-TFP nanosheets, CC3 organic molecular cage nanoparticles and TpPa nanosheets.
5. The preparation method according to claim 1, characterized in that: In step (1), the concentration of the covalent organic framework material dispersion is 0.01-0.2 mg / mL.
6. The preparation method according to claim 1, characterized in that: In step (1), the volume ratio of the m-phenylenediamine solution to the covalent organic framework material dispersion is (5-15):(3-10).
7. The preparation method according to claim 1, characterized in that: In step (1), the electrostatic spraying device performs spraying under the action of an electric field of 6-15 kV.
8. The preparation method according to claim 1, characterized in that: In step (2), the specific method of the post-treatment is: immersing the initial covalent organic framework reverse osmosis membrane in a sodium persulfate aqueous solution and a sodium hydroxide aqueous solution in sequence.
9. The preparation method according to claim 1, characterized in that: In step (2), the concentration of the sodium persulfate aqueous solution is 20-50 g / L, and the concentration of the sodium hydroxide aqueous solution is 5-20 g / L.
10. The composite reverse osmosis membrane prepared by the method according to any one of claims 1 to 9.
